Odpowiedzi

2010-04-15T15:45:22+02:00
0=x-1-(3x-5)
0 = x -1 - 3x -5
0+1+5 = x -3x
6 = -2x | : ( -2)
-3 = x

2x-(1-x)=11-x
2x -1 - x = 11 - x
2x - x + x = 11 +1
2x = 12 | :2
x = 6

2-x/6+x-4/2=3x+5/3
2 - x/6 + x - 4/2 = 3x + 5/3 | *6
2 * 6 - x/6 * 6 + 6*x - 4/2 *6 = 3x *6 + 5/3 * 6
12 - x + 6x - 12 = 18x + 10
12 -12 -10 = 18x -6x + x
-10 = 13x | : 13
- 10/13 = x
1 5 1
2010-04-15T15:54:40+02:00
0=x-1-3+5
-x=-3+5-0
-x=2
x=-2

2x-(1-x)=11-x
2x-1+x=11-x
3x+x=11+1
4x=12
x=3

.2-x/6+x-4/2=3x+5/3 /*6
2-x + 3(x-4)=2(3x+5)=
2-x+3x-12=6x+10
-x+3x-6x=10-2+12
-4x=20
x=-5
1 5 1